Knowledge and Perceptions About Mobile E-Commerce Technologies in Kosovo - Qarkaxhija, Jusuf; Prevalla, Blerta; Latifi, Shpëtim (International Journal of Interactive Mobile Technologies (iJIM), 2022)
Abstract - The enormous increase of online shopping, sales and online orders is disproportionate to the knowledge of the users of these services. The purpose of this paper is to understand how online shopping and orders are perceived by people who are directly or indirectly involved in online e commerce services. The study utilized questionnaires in the collection of data. Data was analyzed using Excel and percentages. Based on the results of the conducted study, it was revealed that very few people know how to distinguish between online shopping and online orders. The same hypothesis can be used to explain what e-commerce is.